MATERIAL AND ENERGY FLOW MANAGEMENT- LIFELONG LEARNING COURSES EXPERIENCES - Zavargo, Z.; Jokić, A.; Pavličević, J.; Ikonić, B.; Bera, O. (Journal of Engineering & Processing Management, 2016)
Material and energy flow management is among the most important factors for the economic growth of a society in harmony with nature and it will play the main role only in the area of sustainable development. The three lifelong learning courses were developed in order to introduce this concept to the industry professionals and administration at the city and regional level. The main goal was to heighten awareness of participants to this topic, as in Serbia it is relatively new approach in corporate and administrative management. The results of the courses confirmed the interest in this kind of lifelong learning courses with suggestion to join it in a single course with emphasise on the specific participant’s problems.